Pleasure and Variety in Thomas More's Utopia. (June 2016) - Vilar, Mariano A.
Abstract : The goal of this article is to provide a better understanding of the organization of pleasure ( voluptas ) in the moral philosophy and in the social practices of the inhabitants of Utopia, the fictional island created by Thomas More. For this purpose, we will focus on the classifications of pleasure into a series of species which tend to suppress the individual nature of pleasure and its connection to subjectivity in order to establish the traits of "natural pleasures, " which fit perfectly the social organization of the island. Our main hypothesis is that this is accomplished by breaking the connection of pleasure and "variety" ( varietas ), which was firmly established by many of the authors (ancient or modern) that discussed this topic. In this article, we argue that the use of the Epicurean texts circulating at the beginning of the 16 th century were instrumental in the elaboration of a theory of "negative pleasures" which are used to keep the homeostasis of the society in Utopia .